2008
DOI: 10.1002/hyp.7162
|View full text |Cite
|
Sign up to set email alerts
|

Glacier change in western North America: influences on hydrology, geomorphic hazards and water quality

Abstract: Abstract:The glaciers of western Canada and the conterminous United States have dominantly retreated since the end of the Little Ice Age (LIA) in the nineteenth century, although average rates of retreat varied from strong in the first-half of the twentieth century, with glaciers stabilizing or even advancing until 1980, and then resuming consistent recession. This retreat has been accompanied by statistically detectable declines in late-summer streamflow from glacier-fed catchments over much of the study area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
290
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(299 citation statements)
references
References 143 publications
(127 reference statements)
9
290
0
Order By: Relevance
“…This contrasts to SF watersheds, where snowmelt percolates through soils before reaching streams. Additionally, nitrification of snow and icemelt NH 4 + in subglacial environments is a mechanism for NO 3 -production. Isotopic studies of aqueous NO 3 -in an Arctic glacier system on Svalbard revealed that this mechanism explained more than 80% of the increase in NO 3 -concentrations observed between supra-and subglacial streams, whereas contributions from rock-derived NH 4 + appeared minimal (38).…”
Section: Low Nomentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts to SF watersheds, where snowmelt percolates through soils before reaching streams. Additionally, nitrification of snow and icemelt NH 4 + in subglacial environments is a mechanism for NO 3 -production. Isotopic studies of aqueous NO 3 -in an Arctic glacier system on Svalbard revealed that this mechanism explained more than 80% of the increase in NO 3 -concentrations observed between supra-and subglacial streams, whereas contributions from rock-derived NH 4 + appeared minimal (38).…”
Section: Low Nomentioning
confidence: 99%
“…Additionally, nitrification of snow and icemelt NH 4 + in subglacial environments is a mechanism for NO 3 -production. Isotopic studies of aqueous NO 3 -in an Arctic glacier system on Svalbard revealed that this mechanism explained more than 80% of the increase in NO 3 -concentrations observed between supra-and subglacial streams, whereas contributions from rock-derived NH 4 + appeared minimal (38). Additional hypotheses, including those involving rock glaciers and landscape development, are discussed elsewhere (7,13,39,40), although we note that our analysis of watershed characteristics did not reveal significantly different NO 3 -contributions associated with the extent of talus or vegetation types across GSF versus SF watersheds.…”
Section: Low Nomentioning
confidence: 99%
“…Storm surges enhanced by sea-ice retreat have led to increased coastal erosion and salinization (Jones et al 2009). Glacier melting has exposed new barren alpine areas subject to primary succession (Arendt et al 2009) and affected the geomorphology of glacier-fed river systems (Moore et al 2009). Increasing human populations and industrial activities also contribute to environmental changes (Walker et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In western North America, notable area and volume loss of glaciers (Larsen et al, 2007;Schiefer et al, 2007;Berthier et al, 2010;Bolch et al, 2010) and decreased late-summer flows in glacier-fed rivers (Stahl and Moore, 2006;Moore et al, 2009) have already been observed. On annual timescales, surface runoff in glacierized basins is affected by glacier mass change (Moore and Demuth, 2001) which supplements streamflow in years with thin snowpack or dry summers.…”
Section: Introductionmentioning
confidence: 99%